Effect of aging on the visuomotor control during continuous bimanual movement - Kiani, Kimia; Patel, Maya; Fu, Qiushi (Frontiers in Aging Neuroscience, 2025)
IntroductionSkilled bimanual coordination is an essential component of activities of daily living that relies on complex interactions between the limbs, yet how age-related changes impact asymmetries in visuomotor control during these tasks remains largely unknown. In the present study, we examined both motor performance and visual attention distribution in non-rhythmic continuous bimanual tasks and investigated the effect of aging.MethodsTwelve right-handed young adults (YA) and twelve right-handed older adults (OA) performed a bimanual tracking task in which each hand controlled a cursor using a robotic device to track the upward movement of a horizontal target line simultaneously and independently. We assessed participants’ performance in the symmetric condition, where both hands should perform the same actions to be successful. Additionally, participants performed the task in asymmetric conditions, where either a new force or a change in visuomotor gain was applied to only one hand, requiring participants to adapt by producing distinct actions with two hands. Overt visual attention was assessed by analyzing participants’ gaze fixation patterns during successful task performance.ResultsOur findings revealed that YA experienced greater difficulty with asymmetric visuomotor constraints than asymmetric force constraints, whereas OA showed comparable performance challenges with both types of constraints. Moreover, we found that YA distributed the gaze consistently biased to the right side despite the effect of context asymmetry on tracking errors, while OA distributed their gaze more symmetrically. Lastly, YA demonstrated asymmetrical adaptation, with improved performance in the dominant right hand under left-sided constraints, while OA showed reduced adaptation capabilities.DiscussionThese findings indicate that aging is associated with a reduction in lateralized attention and diminished adaptability to asymmetric task demands during bimanual visuomotor coordination.